complementing the paper
 Internal ∞-Categorical Models of Dependent Type Theory

                  Nicolai Kraus, 2020

Summary. The standard definition of a semicategory consists
of objects, morphisms, composition, and associativity. How
can we say that a given semicategory has identities, i.e. is
a category? The standard answer is to say that the
semicategory has identities which satisfy left-neutrality and

In this short note, I present another definition of the
statement "has-identities" (a.k.a. "is-a-category").
The motivation is that I want "is-a-category" to be a
*property* of a semicategory rather than *data*, i.e. I want
it to be a proposition a.k.a. proof-irrelevant. For a semi-
category where the morphisms form a set, this is already the
case for the standard answer above. However, without this
additional assumption, the standard answer is data.

My new definition of "is-a-category" is "for every object x,
there is an endomorphism i ∈ Hom(x,x) such that i is
an idempotent equivalence". This Agda file shows that this
is a propositional property. I also show below that a semi-
category has idempotent equivalences if and only if it has
standard identities. 

This Agda file is available on GitHub at
The source code can be type-checked with Agda 2.6.1 (or Agda
2.6.2) and makes use of the library HoTT-Agda, using Andrew
Swan's fork that is 2.6.1-compatible:

{-# OPTIONS --without-K #-}

module Identities where
open import HoTT public
open import Iff

{-  A *wild semicategory*, sometimes also known as a *wild 
    semigroupoid*, consists of:
      - Ob: a type of objects;
      - Hom: a type family of morphisms (for increased
        generality possibly in another universe than Ob, but
        it doesn't matter);
      - and an associative binary operation _⋄_.
    This is of course just a "category without identities". 
    Note that we do *NOT* ask for set-truncation; Ob and Hom
    are arbitrary types/type families!

record SemiCategory j₁ j₂ : Type (lsucc (lmax j₁ j₂)) where
  infixr 40 _⋄_
    Ob  : Type j₁
    Hom : Ob  Ob  Type j₂
    _⋄_ :  {x y z}  Hom y z  Hom x y  Hom x z
    ass :  {x y z w} {f : Hom z w} {g : Hom y z} {h : Hom x y}
         (f  g)  h == f  (g  h)

{-  For the rest of this file, we assume that C is a given
    fixed wild semicategory. We work inside a module which
    fixes C.

module _ {j₁ j₂} (C : SemiCategory j₁ j₂) where
  open SemiCategory C
  j = lmax j₁ j₂

  {- A "standard identity" is a morphism which is left and 
     right neutral. This is the normal, well-known definition.

  module _ {y : Ob} (i : Hom y y) where
    is-left-neutral = {x : Ob} (f : Hom x y)  i  f == f
    is-right-neutral = {z : Ob} (g : Hom y z)  g  i == g
    is-standard-id = is-left-neutral × is-right-neutral

  {- We say that a semicategory (here, the semicategory C)
     is a *standard category* if every object comes with
     a morphism which is left- and right-neutral. This is
     the usual definition of what it means to "have
     identities". -}
  is-standard-category = (x : Ob)  Σ (Hom x x) is-standard-id

  {- The problem with these identities is that "having
     standard identities" is not a propositional property: 
     it is structure, i.e. C can have standard identities in
     multiple different ways. This makes "having standard 
     identities" ill-behaved, as demonstrated in the paper
     (see Example 9, initial model in the wild/incoherent

     We now develop an alternative, and better, definition
     of identities, namely *idempotent equivalences*, and 
     this will lead to a propositional property.

  is-idpt : {x : Ob} (f : Hom x x)  Type j₂
  is-idpt f = f  f == f
  {- Note: `is-idpt f` a.k.a. "f is idempotent" is not
     necessarily a proposition (as 'Hom x x' might not be a
     set). -}

  is-eqv : {x y : Ob} (g : Hom x y)  Type j
  is-eqv {x} {y} g =   ((z : Ob)  is-equiv λ (h : Hom y z)  h  g)
                     × ((w : Ob)  is-equiv λ (f : Hom w x)  g  f)
  {- Note: `is-eqv g` a.k.a. "g is an equivalence" is a
     proposition. This is automatic, as `is-equiv` (the
     analogous property for types) is a proposition. -}

  is-idpt+eqv : {x : Ob} (i : Hom x x)  Type j
  is-idpt+eqv i = is-idpt i × is-eqv i
  {- Note: `is-idpt+eqv i` a.k.a. "being idempotent and an 
     equivalence" is still not not a proposition!
     E.g. in the wild semicategory of types and functions,
     the identity on the circle S¹ is an idempotent 
     equivalence in ℤ-many ways. -}

  {- I define "being a good category" as a property of a 
     semicategory. The property states that each object
     comes with an idempotent equivalence. -}

  is-good-category = (x : Ob)  Σ (Hom x x) is-idpt+eqv
  {- Note: "being a category" a.k.a. "having idempotent
     equivalences" *is* a proposition, but this is not
     trivial. The main goal of the current file is to prove
     this result.

     First, we show that an idempotent equivalence is also a
     standard identity. -}
  module idpt+eqv→std {y : Ob} (i : Hom y y)
                      (idpt+eqv : is-idpt+eqv i) where

    idpt = fst idpt+eqv
    eqv = snd idpt+eqv

    {- The idempotent equivalence i is left neutral: -}
    left-neutral : is-left-neutral i
    left-neutral f = w/o-i
        with-i : i  (i  f) == i  f
        with-i =
          i  (i  f)
            =⟨ ! ass 
          (i  i)  f
            =⟨ ap  g  g  f) idpt 
          i  f
        w/o-i : i  f == f
        w/o-i = is-equiv.g
                  (ap-is-equiv {f = λ g  i  g} (snd eqv _) (i  f) f)

    {- The proof of right neutrality is completely symmetric
       to the above. Here is the shortened version: -}
    right-neutral : is-right-neutral i
    right-neutral g =
        (ap-is-equiv (fst eqv _) (g  i) g)
        (ass  ap  f  g  f) idpt)

  {- The above shows that an idempotent equivalence is a
     standard equivalence. A "summary statement" will be given
     We start the opposite direction with very simple
     observation: Any left-neutral endomorphism is idempotent. -}
  left-neutral→idempotent : ∀{y} (f : Hom y y) 
                                 is-left-neutral f  is-idpt f
  left-neutral→idempotent f l-ntrl = l-ntrl f
  {- Of course, the same is true for right-neutral
     endomorphisms, but the above suffices for us.

     We are now ready to prove that a standard identity is an
     idempotent equivalence. -}
  module std→idpt+eqv {y : Ob} (i : Hom y y)
                      (std-id : is-standard-id i) where

    l-ntrl = fst std-id
    r-ntrl = snd std-id

    eqv : is-eqv i
    eqv =  z  is-eq  g  g  i)  h  h) r-ntrl r-ntrl)
          λ x  is-eq  f  i  f)  h  h) l-ntrl l-ntrl

    idpt : is-idpt i
    idpt = left-neutral→idempotent i l-ntrl

  {- "Summary statement":
     We now have everything in place to state that an
     endomorphism `i` is an idempotent equivalence if and
     only if it is a standard identity. -}

  idpt+eqv⇔std : ∀{y}  (i : Hom y y) 
                        is-idpt+eqv i  is-standard-id i
  idpt+eqv⇔std i = ( , )
       : is-idpt+eqv i  is-standard-id i
       p = idpt+eqv→std.left-neutral i p , idpt+eqv→std.right-neutral i p
       : is-standard-id i  is-idpt+eqv i
       p = std→idpt+eqv.idpt i p , std→idpt+eqv.eqv i p

  {- This implies that any two idempotent equivalences are equal. -}

  idpt+eqv-unique : ∀{y}  (i₁ i₂ : Hom y y) 
                    is-idpt+eqv i₁  is-idpt+eqv i₂  i₁ == i₂
  idpt+eqv-unique i₁ i₂ p₁ p₂ =
      =⟨ ! (idpt+eqv→std.right-neutral i₂ p₂ i₁) 
    i₁  i₂
      =⟨ idpt+eqv→std.left-neutral i₁ p₁ i₂ 

  {- A useful property is 2-out-of-3 for equivalences:
     If we have g ∘ f == h and two out of the three maps
     {f, g, h} are equivalences, then so is the third.
     Here, we only show (and need) one instance, namely
     that it suffices if g and h are equivalences. 
     This is easy but a bit tedious. -}

  eqv-2-out-of-3 : ∀{w x y} (f : Hom w x) (g : Hom x y)
     is-eqv g  is-eqv (g  f)  is-eqv f
  eqv-2-out-of-3 {w} {x} {y} f g (p₁ , p₂) (q₁ , q₂) =
     _  -⋄f-is-eqv)
     _  f⋄-is-eqv)
      {- first part -}
      -⋄f : {y : Ob}  Hom x y  Hom w y
      -⋄f = λ h  h  f
      -⋄g⁻¹ : {z : Ob}  Hom x z  Hom y z
      -⋄g⁻¹ = is-equiv.g (p₁ _)
      -⋄gf : {z : Ob}  Hom y z  Hom w z
      -⋄gf = λ h  h  (g  f)
      eq' : ∀{z}  -⋄gf {z}  -⋄g⁻¹ == -⋄f {z}
      eq' {z} = λ=  h 
        (-⋄g⁻¹ h)  (g  f)
          =⟨ ! ass 
        ((-⋄g⁻¹ h)  g)  f
          =⟨ ap  k  k  f) (is-equiv.f-g (p₁ _) _) 
        h  f
      -⋄g⁻¹-equiv : ∀{z}  is-equiv (-⋄g⁻¹ {z})
      -⋄g⁻¹-equiv = is-equiv-inverse (p₁ _)
      -⋄f-is-eqv : ∀{z}  is-equiv (-⋄f {z})
      -⋄f-is-eqv {z} = transport is-equiv eq' (q₁ _ ∘ise -⋄g⁻¹-equiv)

      {- second part -}
      f⋄- : {v : Ob}  Hom v w  Hom v x
      f⋄- = λ h  f  h
      g⁻¹⋄- : {v : Ob}  Hom v y  Hom v x
      g⁻¹⋄- = is-equiv.g {f = λ h  g  h} (p₂ _)
      gf⋄- : {v : Ob}  Hom v w  Hom v y
      gf⋄- = λ h  (g  f)  h
      eq : ∀{v}  g⁻¹⋄- {v}  gf⋄- == f⋄- {v}
      eq {v} = λ=  h 
        (g⁻¹⋄-  gf⋄-) h
          =⟨ idp 
        g⁻¹⋄- ((g  f)  h)
          =⟨ ap g⁻¹⋄- ass 
        g⁻¹⋄- (g  (f  h))
          =⟨ is-equiv.g-f (p₂ _) (f  h)  
        (f  h)
          =⟨ idp 
        f⋄- h
      g⁻¹⋄-equiv : ∀{v}  is-equiv (g⁻¹⋄- {v})
      g⁻¹⋄-equiv {v} = is-equiv-inverse (p₂ _)
      f⋄-is-eqv : ∀{v}  is-equiv (f⋄- {v})
      f⋄-is-eqv {v} = transport is-equiv eq (g⁻¹⋄-equiv ∘ise q₂ _)

  {- Given an equivalence, we can define an idempotent
     equivalence. This construction was already presented in
     "Higher Univalent Categories via Complete Semi-Segal Types"
     (Capriotti-Kraus, POPL'18) and is motivated by work of
     Harpaz and Lurie in higher dimensional category theory. -}

  module I {y z} (e : Hom y z) (p : is-eqv e) where

    e⁻¹⋄- : ∀{x}  Hom x z  Hom x y
    e⁻¹⋄- = is-equiv.g (snd p _)

    e⋄- : ∀{x}  Hom x y  Hom x z
    e⋄- = _⋄_ e

    I : Hom y y
    I = e⁻¹⋄- e

    {- In comments, we write I(e) for the I constructed above
       (e is a module parameter).

       It is easy to see that I(e) is right neutral for e: -}
    e⋄I : e  I == e
    e⋄I = is-equiv.f-g (snd p _) e

    {- Also easy (but more work): 
       I is left neutral in general. -}
    l-ntrl : is-left-neutral I
    l-ntrl f =
      I  f
        =⟨ ! (is-equiv.g-f (snd p _) _) 
      e⁻¹⋄- (e⋄- (I  f))
        =⟨ ap e⁻¹⋄- (! ass) 
      e⁻¹⋄- ((e  I)  f)
        =⟨ ap  g  e⁻¹⋄- (g  f)) e⋄I 
      e⁻¹⋄- (e  f)
        =⟨ is-equiv.g-f (snd p _) _ 

    {- We do not need the other analogous properties. This
       is enough to see that I is an idempotent equivalence. -}

    I-is-idpt+eqv : is-idpt+eqv I
    I-is-idpt+eqv = left-neutral→idempotent
      I l-ntrl ,
      eqv-2-out-of-3 I e p (transport is-eqv (! e⋄I) p)

  {- If an endomorphism e is an equivalence, then it is
     idempotent if and only if it is equal to I(e); and
     this connection even forms an equivalence of types
  module e-vs-I {y : Ob} (e : Hom y y) (p : is-eqv e) where
    open I
    e-I-idpt : (e == I e p)  is-idpt e
    e-I-idpt =
      e == I e p
        ≃⟨ ap-equiv (e⋄- e p , snd p _) e (I e p) 
      e  e == e  I e p
        ≃⟨ transport  expr 
           (e  e == e  I e p)  (e  e == expr)) (e⋄I e p) (ide _)  
      e  e == e
        ≃⟨ ide _ 
      is-idpt e

  {- Finally, put all the previous lemmas together to show that
     the type of idempotent equivalences is a proposition. We do
     this by showing that, if we assume that this type has one 
     element i₀, then i₀ is the only element. -}

  module unique (y : Ob) (i₀ : Hom y y)
                (idpt+eqv₀ : is-idpt+eqv i₀) where

    open I
    open e-vs-I
    idpt₀ = fst idpt+eqv₀
    eqv₀ = snd idpt+eqv₀

    {- Using a chain of equivalences, we show that the type
       of idempotent equivalences is trivial (given one
       single idempotent equivalence, see the module
       parameter). -}

    idpt-to-=i₀ =
      Σ (Hom y y)  i  is-idpt+eqv i)
        ≃⟨ ide {i = j} _ 
      Σ (Hom y y)  i  is-idpt i × is-eqv i)
        ≃⟨ Σ-emap-r  i  ×-comm) 
      Σ (Hom y y)  i  Σ (is-eqv i) λ eqv  (is-idpt i))
        ≃⟨ Σ-emap-r  i  Σ-emap-r λ eqv  e-I-idpt i eqv ⁻¹) 
      Σ (Hom y y)  i  Σ (is-eqv i) λ eqv  i == I i eqv)
        ≃⟨ Σ-emap-r  i  Σ-emap-r λ p  coe-equiv
             (ap  i'  (i == i')) (
                 idpt+eqv-unique (I i p)
                                 (I-is-idpt+eqv i p)
      Σ (Hom y y)  i  Σ (is-eqv i) λ _  i == i₀)
        ≃⟨ Σ-emap-r  i  ×-comm) 
      Σ (Hom y y)  i  Σ (i == i₀) λ _  (is-eqv i))
        ≃⟨ Σ-assoc ⁻¹ 
      (Σ (Σ (Hom y y)  i  (i == i₀))) λ ip  (is-eqv (fst ip)))
        ≃⟨ Σ-emap-l {A = Unit}
                    {B = Σ (Hom y y) λ i  (i == i₀)}
                     ip  (is-eqv (fst ip)))
                    (contr-equiv-Unit (pathto-is-contr i₀) ⁻¹) ⁻¹ 
      (Σ Unit λ _  is-eqv i₀)
        ≃⟨ Σ₁-Unit 
      is-eqv i₀
        ≃⟨ contr-equiv-Unit (inhab-prop-is-contr eqv₀) 

    {- In other words, the type of idempotent equivalences 
       is contractible. -}
    unique-idpt+eqv : is-contr (Σ (Hom y y)  i  is-idpt+eqv i))
    unique-idpt+eqv = equiv-preserves-level (idpt-to-=i₀ ⁻¹)

{-                     THEOREMS

   With the help of the above lemmas, we show our main

   (1) A semicategory is a good category if and only if
       it is a standard category.

   (2) "Being a good category" is a propositional (proof-
       irrelevant) property of a semicategory.

good-iff-standard :  {j₁ j₂} (C : SemiCategory j₁ j₂) 
                    is-good-category C  is-standard-category C
good-iff-standard C =  , 
   : is-good-category C  is-standard-category C
   igc x = fst (igc x) , fst (idpt+eqv⇔std C _) (snd (igc x))
   : is-standard-category C  is-good-category C
   isc x = fst (isc x) , snd (idpt+eqv⇔std C _) (snd (isc x))

goodness-is-prop :  {j₁ j₂} (C : SemiCategory j₁ j₂) 
                             is-prop (is-good-category C)
goodness-is-prop C = inhab-to-contr-is-prop λ idpt+eqvs 
  WeakFunext.weak-λ= λ y  unique.unique-idpt+eqv C y
                                                  (fst (idpt+eqvs y))
                                                  (snd (idpt+eqvs y))